178 Outcomes After Paediatric Extracorporeal Cardiopulmonary Resuscitation (ECPR) In A Tertiary Centre. (12th October 2021) - Ashry, A; Harky, A; Abousteit, A; Smith, T; Brady, A; Horan, M; Nolan, S; Lotto, A; Guerrero, R; Dhannapuneni, R
Abstract: Objective: To report our outcomes in utilizing extracorporeal membrane oxygenation (ECMO) institution for cardiac arrest. Method: Retrospective records of all patients that needed ECPR between January 2015 and July 2020 have been reviewed. Primary outcomes were survival to ECMO decannulation, hospital discharge and one year survival. Secondary outcomes were the need for ECMO re-cannulation and neurology outcome using Paediatric Cerebral Performance Category (PCPC). Results: A total of 44 consecutive patients were identified. 75 % were post cardiac surgery (n = 33), mean time from arrest to initiation of ECMO was 39.5 mins +/- 17.7 mins. Mean highest lactate prior to ECMO was 12.9 +/- 4.4. 79.6 % of patients received central cannulation. 11.4 % of patients (n = 5) needed more than one run of ECMO. Mean hours on ECMO were 175.4 +/- 212.5 hours and mean PCPC score was 2.14 +/- 1.68. Mean ICU stay was 16.2 +/- 16.9 days and total hospital stay was 47 +/- 68.5 days. Overall Survival to ECMO weaning was 68.4 % (n = 13) vs 92 % (n = 23) in neonates and paediatric patients, respectively. Survival to hospital discharge was 47.4 % (n = 9) vs 72 % (n = 18) and one year survival was 42.1 % (n = 8) vs 72 % (n = 18) in the neonatal and paediatric cohort, respectively. Conclusions: Our survival rates are encouraging and in line with current published literature and comparable favourably to International ELSO (Extracorporeal life support organisation) registry for neonates and paediatric patients of all cause ECPR. Paediatric patients showed a survival advantage over neonates after ECPR.